2007
DOI: 10.1007/bf02849896
|View full text |Cite
|
Sign up to set email alerts
|

Clear cystic fluid in hepatic hydatidosis does not rule out communication between cysts and the biliary system

Abstract: Hydatid cysts (HCs) of the liver are a major problem in the areas to which they are endemic. Approximately 15% of hepatic cysts have been shown to communicate with the biliary system. In 2 cases in which patients were undergoing HC surgery, the cystic fluid appeared to be clear, but after the germinative membranes were removed, a connection with the biliary system could be seen. This observation suggests that the decision to inject a scolicidal or sclerosing agent during surgery should be evaluated carefully, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A very interesting study on the histopathology of the pericyst [20] showed the surprisingly constant finding of small areas of fibrinoid necrosis where the fistula is going to develop. Furthermore, the appearance of bile from the drain is very common after 24-48 hours after percutaneous puncture of large diameter hydatid cyst, as the tension inside the cyst diminish as it is quite frequent the development of "late" biliary fistulas after not radical surgery [21].…”
Section: Discussionmentioning
confidence: 99%
“…A very interesting study on the histopathology of the pericyst [20] showed the surprisingly constant finding of small areas of fibrinoid necrosis where the fistula is going to develop. Furthermore, the appearance of bile from the drain is very common after 24-48 hours after percutaneous puncture of large diameter hydatid cyst, as the tension inside the cyst diminish as it is quite frequent the development of "late" biliary fistulas after not radical surgery [21].…”
Section: Discussionmentioning
confidence: 99%
“…Important cautionary measures are the following: (1) perioperative treatment with albendazole and protection of the surgical field with pads soaked with scolicidal agents to prevent secondary CE and relapses; (2) avoidance of scolecidal agents, in case of open surgery, if cystobronchial or cysto-biliary fistulae are observed (the latter by visualization of the fistula, presence of bile-stained cystic fluid, detection of bilirubin in the fluid, or by cholangiography); and (3) appropriate management of the residual cavity (Junghanss et al 2008). Of note, any connection with the biliary system can be visualized only after reduction of the intracystic pressure; hence, the presence of clear fluid does not rule out cysto-biliary fistulae (Sonmez et al 2007). …”
Section: Surgerymentioning
confidence: 98%
“…In 2 cases in which patients were undergoing hydatid cyst surgery, the cystic fluid appeared to be clear, but after the germinative membranes were removed, a connection with the biliary system could be seen. Endoscopic retrograde cholangiopancreatography may not help to differentiate between them because of suspected communication between the bile duct and the hydatid cyst [ 11 ]. It has been suggested that small areas of fibrinoid necrosis within the fibrous pericyst may be an explanation for this communication [ 12 ].…”
mentioning
confidence: 99%